The 10-year anniversary of intense protest in Greece and the role of Facebook - Papa, Venetia; Ioannou, Maria (My University, 2023)
This study provides a comparative analysis of collective meaning-making processes by unpacking activists’ discourses (within and in relation to their polis) and online (on Facebook) during the financial, post-financial, and COVID-19 crises in Greece (2011–2021). By analyzing 71 semi-structured interviews with activists and 14,475 Facebook posts, we first evaluate actors’ identity progression, then identify the differences and commonalities between activists’ discourses attached to their collectivity, by investigating the role of Facebook therein. Our findings indicate that activists’ efforts to delimitate their identity, primarily around the detachment of citizens from their polis, paved the way for the (re)invention of the meaning-making practices of each collectivity. Thus, the formation of an overarching identity of the citizen as an activist-subject unites subjects over power struggles, despite their political differences.
Keywords: Social movements; Indignados; Irianna’s movement; COVID-19; Collective identity; Facebook; Greece